Technology and Copyright Law: A Guidebook for the Library, Research, and Teaching Professions - Bielefield, Arlene; Cheeseman, Lawrence (Libraries & the law series, 1997)
"Explains the intent of copyright law, how it developed, and where it is headed; provides guidance for making copyright decisions; and discusses the electronic classroom and international copyright agreements."
Keywords: Fair use (Copyright); Law and legislation; United States; United States; Information services; United States; Library legislation; dept.ils; faculty_collection